Hybrid solid electrolyte
By introducing permeable ceramic phase into the solid electrolyte, an improved ionic conductivity hybrid interface layer is formed, and the problem of poor battery performance of solid polymer electrolytes at room temperature is solved, and better conductivity and low-temperature performance is achieved.
Patent Information
- Application Number
- CN201980085785.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-19
- Filing Date
- 2019-12-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2039-12-19
AI Technical Summary
When used in ambient conditions (such as room temperature), existing solid polymer electrolytes lead to poor battery performance, mainly due to the high contact resistance between the polymer electrolyte and the metal electrode material, and the reduction of body ion conductivity at low temperatures.
By providing a solid electrolyte comprising a polymer matrix having a permeable ceramic phase, specifically including an ionically conductive matrix of the polymer, a dispersed metal salt and a first ceramic material, the ceramic material penetrates to at least one side of the ionically conductive matrix to form an improved ionically conductive hybrid interface layer.
This technical method effectively reduces the interface resistance, improves the body ion conductivity and ion migration number of solid electrolytes, and improves the performance of the battery under low temperature conditions.
Smart Images

Figure CN113228369B_ABST
Abstract
Description
[0001] Technical Field and Background
[0002] The present disclosure relates to solid polymer electrolytes for alkaline (earth) metal batteries and methods for making the same.
[0003] In batteries based on alkaline (earth) metals, the negative electrode includes an electrochemically active metal. Due to safety issues, for example, due to flammability, the current situation in metal ion batteries (such as lithium ion batteries with liquid electrolytes) is not suitable for application in metal batteries. Instead, solid electrolytes such as polymers and ceramic electrolytes can be used. Polymer-based electrolytes may be preferred compared to ceramic electrolytes because such materials are easier to process. However, the use of solid polymer electrolytes under ambient conditions (such as at room temperature) often results in poor battery performance. It is believed that poor battery performance may stem from the high contact resistance between the polymer electrolyte and the metal electrode material. In addition, when the temperature is reduced, the bulk ion conductivity of the solid electrolyte decreases. In the case of polymer electrolytes, at lower temperatures, the internal flow of the polymer chains is less. For example, an incompatible interface with high resistance can be formed. Better performance can be obtained by operating the metal-polymer-battery at an elevated temperature. The lithium metal polymer battery produced by Blue Solutions SA (a subsidiary of the Bolleroy Group) contains a polymer electrolyte and operates at a temperature above 60°C to obtain good performance. In electronic devices, the electronic circuit can be equipped with a current collector such as the type in electrochemical devices. For example, the electrochemical device is a battery, such as a rechargeable Li-ion solid-state battery with a current collector of non-planar design. In the discharge battery mode, the anode is the "negative electrode" to which the positive current flows from the cathode, which is the "positive electrode". During charging, these functions are reversed. Regardless of the charging mode, the electrochemical relationship can be characterized by the exchange of charge between the negative electrode material and the positive electrode material, the negative electrode material having a lower work function or redox potential than the work function or redox potential of the positive electrode material.
[0004] For example, known negative electrode (anode during battery discharge) materials are Li4Ti5O12 (lithium titanate spinel or LTO); LiC6 (graphite); Li4.4Si (silicon) and Li4.4Ge (germanium). Known positive electrode (cathode) materials are LiCoO2 (lithium cobalt oxide or LCO), LiCoPO4, (doped) LiMn2O4 (lithium manganese oxide spinel or LMO), LiMnPO4, LiFePO4 (LFP), LiFePO4F (LFPF) or LiCo1 / 3Ni1 / 3Mn1 / 3O2 (LCNMO).
[0005] Thin film batteries, including those of thin film solid-state lithium-ion types, can be prepared by various deposition techniques to make negative electrodes, positive electrodes, and electrolyte materials that are combined together to form a battery. Such techniques can typically include depositing a thin film of such material using vacuum deposition or other techniques that result in similar thin films to produce a "thin film" battery. Thin film batteries are often used in applications where space and weight can be preferably saved and where extremely long cycle life can be expected. When a battery containing a polymer solid electrolyte is operated at high temperatures, the polymer electrolyte softens, which makes the system susceptible to dendrite growth. US2018026302 describes a porous polyethylene separator for use in combination with a liquid electrolyte, which is coated with a ceramic material to prevent dendrite expansion. However, the electrolyte described does not solve the contact resistance problem, and a liquid electrolyte is used, which can lead to safety issues, such as when the battery temperature is high and the liquid electrolyte may catch fire due to a short circuit.
[0006] Alternatively, ion-conducting ceramic materials can be used as electrolyte materials. Such materials can form a more compatible interface with electrode materials. However, such ceramic electrolyte materials typically have limited bulk ionic conductivity and are also typically difficult to handle and very brittle, which makes batteries containing solid ceramic electrolytes prone to rupture and / or other forms of failure. A publication by S. Zekloll et al. in Energy & Environmental Science, 2018, 11, pages 185-201 describes a microporous 3D-printed ion-conducting ceramic electrolyte structure in which the pores are filled with polypropylene or epoxy polymers. The disclosed polymer / ceramic microstructured electrolyte exhibits improved mechanical properties, but at the expense of ionic conductivity.
[0007] Therefore, there is a need to provide solid-state electrolytes that combine good bulk ionic conductivity, ion transference number, and low interfacial resistance.
[0008] The present disclosure is directed to providing solid-state electrolytes and methods of making the same that alleviate one or more of the aforementioned limitations by providing a solid-state electrolyte comprising a polymer matrix with an infiltrating ceramic phase. Summary of the invention
[0009] Aspects of the present disclosure relate to a solid electrolyte suitable for providing an ion-conductive connection between a negative electrode and a positive electrode in a battery. The solid electrolyte comprises an ion-conductive matrix comprising a polymer, a metal salt dispersed in the ion-conductive matrix, and a first ceramic material, wherein at least one side of the ion-conductive matrix for connection to the negative electrode or the positive electrode is infiltrated by the first ceramic material to form a first mixed interface layer with improved ion conductivity between at least one of the negative electrode and the positive electrode in the battery and the ion-conductive matrix.
[0010] In some embodiments, the present disclosure relates to a solid electrolyte in which both sides of the ion-conducting matrix for connection to an electrode of a battery are infiltrated with a ceramic material to form a first and a second mixed layer. The second mixed layer may include a second ceramic material different from the first ceramic material. Alternatively, the second mixed layer may include the same ceramic material as the first mixed layer.
[0011] In some preferred embodiments, one or more faces of the ion-conducting matrix for connection to an electrode are provided with a first covering layer. The first covering layer comprises one or more of: an ion-conducting ceramic material; and a ceramic material that forms an ion-conducting material by a reaction between the ceramic material and a negative electrode material.
[0012] Aspects of the present disclosure also relate to methods for making the disclosed solid electrolytes and products obtainable therefrom. The methods include: providing an ion-conducting matrix comprising a polymer and a dispersed metal salt; and exposing a first face of the ion-conducting matrix to a vapor-phase ceramic precursor material. The vapor-phase ceramic precursor material infiltrates the ion-conducting matrix and reacts with a co-reactant to form a mixed layer. This infiltration potentially results in dispersion of ceramic (nano) particles within the polymer matrix and can help increase ionic conductivity through it.
[0013] The co-reactant comprises one or more of the group consisting of water, hydrogen sulfide and oxidizing plasma. In some embodiments, the co-reactant can be provided to the ion conductive matrix 10m from the gas phase. Alternatively or additionally, when the co-reactant is water, the co-reactant can be present in the ion conductive matrix. For example, in the step of forming the ion conductive matrix, an appropriate amount of water can be introduced into the ion conductive matrix.
[0014] In some preferred embodiments, the method includes providing a ceramic covering layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] These and other features, aspects, and advantages of the apparatus, systems, and methods of the present disclosure will become better understood from the following description, appended claims, and accompanying drawings, in which:
[0017] Figure 1A A battery stack including a solid electrolyte prone to dendrite formation is shown;
[0018] Figure 1B A battery stack including a solid electrolyte including a first mixed layer is shown;
[0019] Figures 2A-2DFour exemplary embodiments of solid-state electrolytes are shown, including mixed layers and / or capping layers at one or more faces of the solid-state electrolyte for connection to a negative electrode or a positive electrode in a battery;
[0020] Figure 3A A multilayer solid electrolyte formed by a stack of solid electrolyte layers is shown;
[0021] Figure 3B-3C Exemplary 2D-batteries and 3D-batteries including solid-state electrolytes are shown. DETAILED DESCRIPTION
[0022] The terms used to describe specific embodiments are not intended to limit the present invention. As used herein, the singular forms "one", "a kind of" and "said" are intended to also include plural forms, unless the context clearly indicates otherwise. The term "and / or" includes any and all combinations of one or more related listed items. It should be understood that the terms "include" and / or "comprise" specify the presence of the features, but do not exclude the presence or addition of one or more other features. It should also be understood that when a particular step of a method is referred to as being after another step, it may be directly after the other step, or one or more intermediate steps may be implemented before implementing a particular step, unless otherwise stated. Similarly, it should be understood that when describing a connection between a structure or component, the connection may be established directly or through an intermediate structure or component, unless otherwise stated.
[0023] The present invention is described more fully hereinafter with reference to the accompanying drawings, in which embodiments of the present invention are shown. In the accompanying drawings, the absolute and relative sizes of systems, components, layers and regions may be exaggerated for clarity. The embodiments are described with reference to schematic and / or cross-sectional illustrations of possible idealized embodiments and intermediate structures of the present invention. In the specification and drawings, the same figure numbers represent the same elements throughout. Relative terms and their derivatives should be interpreted as referring to the direction described at the time or the direction shown in the drawings under discussion. These relative terms are for ease of description and do not require the system to be manufactured or operated in a specific direction unless otherwise specified.
[0024] Figure 1A A cross-sectional view of a comparative battery stack 100 is schematically shown. The comparative battery stack described comprises a solid bottom current collector 6, a solid negative electrode layer 2 (anode), a solid electrolyte layer 1 composed of a mixture of a metal salt and an ion-conducting polymer, a solid positive electrode layer 3 (cathode) and a solid top current collector 5. The solid electrolyte layer serves as a layer that facilitates the transport of ions from the negative electrode to the positive electrode during the discharge cycle of the battery, or in other words conducts ions, and vice versa during the charge cycle of the battery. Typically, the negative electrode comprises lithium metal and the solid electrolyte comprises a polymer matrix suitable for conducting lithium ions. Figure 1AIt further shows typical dendrite formation problems which may occur for such cells when operated, for example, at elevated temperatures, for example at temperatures above 60°C.
[0025] Without wishing to be bound by theory, it is believed that during the charging cycle, lithium ions are transported through the solid electrolyte layer and reduced to an electrochemically active state at the interface with the negative electrode. However, instead of forming a uniform electrode layer, dendrites D, such as sharp needles or spikes, can form electrode materials that are inserted outward into the solid electrolyte layer. Such dendrites can grow until they eventually pierce the solid electrolyte layer and reach the positive electrode material, where they cause a dangerous short circuit SC. It is believed that many factors play an important role in this process. In addition to operating conditions such as charging rate, temperature and potential, these factors also include: electrolyte layer thickness, electrolyte layer hardness and field distribution during charging. Uneven field distribution may lead to uneven and localized electrode material deposition, which can lead to further uneven field distribution and thus exacerbate dendrite formation. Soft and / or thin solid electrolyte layers further increase the risk of dendrite formation.
[0026] Figure 1B A cross section of a battery 101 including a solid electrolyte 10 according to one or more aspects of the present invention is schematically shown. The battery is formed by a stack of layers including a negative electrode 2 and a positive electrode 3 separated from each other by a solid electrolyte 10. The top and bottom current collectors are not shown. According to one aspect of the present invention, the solid electrolyte 10 includes an ion-conducting matrix 10m. In the embodiment shown, the solid electrolyte 10 includes a mixed layer 10h and a covering layer 10c on the face connected to the negative electrode. The thickness z of the mixed layer 10h is shown. The thickness z of the mixed layer is preferably 10nm to at most 50μm, more preferably 50nm to 20μm, and most preferably 100nm to 10μm, for example 250nm or 1μm. Alternatively or additionally, the solid electrolyte can span most of the thickness of the solid electrolyte layer.
[0027] According to a first aspect, a solid electrolyte 10 disclosed herein comprises an ionically conductive matrix 10m. The disclosed solid electrolyte 10 is suitable for providing an ionically conductive connection between a positive electrode and a negative electrode of a battery (eg, a rechargeable battery).
[0028] The negative electrode (anode) of the battery may comprise one or more metals of Li, Na, K, Mg, Ca and Al, silicon and tin, graphite. Alternatively or additionally, the negative electrode may comprise a conversion material, such as the corresponding metal oxide MO, or a mixture thereof. The positive electrode (cathode) may comprise an insertion or conversion based material. Suitable materials may, for example, be selected from metal oxides, silicon, graphite materials, sulfur, phosphates, oxygen and air. For lithium ion batteries, it may, for example, include LiCoO2, MnO2, LiMn2O4, LiNiO2, Lix Mn y Ni z O2、LiNi 1-x Co x O2、LiNi x Co y Al z O2、Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2、Li(Ni x Mn y Co 1-x-y )O2、Li(Li x Mn y Ni z Co 1-x-y-z )O2, LiFePO4, Li2FePO4F, V2O5, V2O5-TeO2, WO3-V2O5, TiS x O y 、Metal Oxide MO x 、Metal fluoride MF x 、Metal chloride MCl x 、Metal sulfide MS x or Li-V2O. For other ion insertion type batteries, the positive electrode layer may, for example, comprise materials similar to those listed above for lithium ion batteries, but with Li replaced by other ions. For example, for Na ion batteries, the first electrode layer 12 may, for example, comprise NaMn2O4; for Mg ion batteries, the first electrode layer may, for example, comprise MgMn2O4; and for Al ion batteries, the first electrode layer may, for example, comprise Al x V2O3, the present disclosure is not limited thereto.
[0029] According to another aspect, the ion-conducting matrix comprises a polymer P and a metal salt S. Preferably, the metal salt S is dispersed in the ion-conducting matrix 10m. The ion-conducting matrix 10m forms an ion-conducting medium. Figure 1B It can be clearly seen that the medium can be a single continuous layer. For example, the ion conductive matrix 10m can form a uniform material layer. Alternatively or in addition, the ion conductive matrix 10m can include nanopores. In the case where the medium is a dense material, there can still be a small gap, for example, in the form of a gap space. Such a gap can, for example, be present between adjacent polymer chains contained in the medium. Alternatively or in addition, other gaps can exist in the form of (nano) holes. In some embodiments, the ion conductive matrix 10m can include a gelled polymer.
[0030] The ion-conducting matrix 10m generally comprises a polyether polymer. Such a polymer may be selected from, but not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), polybutylene oxide, and / or blends and / or derivatives thereof, such as block copolymers. The ion-conducting matrix 10m also comprises a metal salt, preferably a metal salt comprising a weakly coordinated anion, such as, but not limited to, perchlorate (ClO4), bis(trifluoromethane)sulfonyl imide (TFSI), bis(fluorosulfonyl)imide (FSI) and fluorophosphate (PF6). Alternatively or in addition, the ion-conducting matrix 10m may also comprise a gel-based electrolyte, such as a gelled mixture of a polymer and a liquid electrolyte or other additives, such as succinonitrile and / or an ionic liquid.
[0031] Preferably, the metal salt S comprises metal ions corresponding to the metal contained in the negative electrode of the battery, for which the solid electrolyte 10 is suitable. For example, for a battery stack in which the negative electrode comprises metallic lithium, the metal salt S comprises lithium ions.
[0032] According to another aspect, the ion-conducting matrix 10m comprises a first ceramic material C1. The material is disposed on the ion-conducting matrix 10m such that at least one side of the ion-conducting matrix 10m for connection to the negative electrode or the positive electrode is infiltrated by the first ceramic material C1. In some preferred embodiments, the thickness of the ion-conducting matrix 10m is less than 100 microns, preferably less than 25 microns, for example, 25 to 5 microns, or 10 to 1 micron.
[0033] By penetrating the ion-conducting matrix 10m, it can be understood that the ceramic material penetrates into the solid electrolyte layer 10 from one side toward the main body. In some preferred embodiments, the first ceramic material C1 penetrates into the ion-conducting matrix 10m to form a first mixed layer 10h1 extending from the first side of the solid electrolyte 10 to the main body of the solid electrolyte. The thickness z of the first mixed layer is preferably at least 1% of the thickness of the ion-conducting matrix 10m. Optionally, the first mixed layer can be thicker (ticker), for example 5%, 20%, 50% or more, up to 100%, extending all the way to the opposite side of the ion-conducting matrix 10m.
[0034] In some preferred embodiments, the ceramic is formed in small ceramic domains. Preferably, the ceramic domains include at least one dimension on a mesoscopic scale. In other words, the ceramic domains in the mixed layer preferably have at least one dimension, such as a diameter, whose size is greater than the atomic scale but less than the macroscopic scale. For example, the mesoscopic ceramic domains include at least one dimension of 1 nm to 5 μm, preferably 5 nm to 1 μm, and more preferably 10 nm to 500 nm.
[0035] The increased interface area between the polymer matrix and the infiltrated ceramic surface can reduce the contact resistance between the electrode and the formed solid electrolyte 10. In all polymeric solid electrolytes, the interfacial contact resistance is believed to be controlled by the interface area between the polymer and the electrode. By producing a mixed material, the interface resistance can be separated into the interfacial contact resistance between the ceramic and the electrode and the interface resistance between the polymer matrix and the ceramic inside the mixed layer. By increasing the area between the ceramic and the ion-conducting matrix 10m, the total interfacial contact resistance can be reduced. The interface area between the ceramic and the ion-conducting matrix 10m can be improved by the following methods: a) infiltrating the polymer matrix with a certain amount of ceramic material, b) reducing the size of the ceramic domains in the mixed layer 10h1, and / or c) forming a mixed layer with an increased volume, such as increasing the thickness of the mixed layer.
[0036] In a preferred embodiment, the mixed layer comprises at least 5% by volume of ceramic material, preferably 10% to 90% by volume, more preferably 20% to 80% by volume, and even more preferably 30% to 60% by volume. Providing more equal volumes of ceramic material and ion-conducting matrix 10m to the mixed layer can increase the interfacial area between these materials. The inventors have found that such penetration can also increase the bulk conductivity of the mixture because the nanoparticles help to reduce the Tg of the polymer matrix.
[0037] The first ceramic material C1 may include one or more of the following: a single oxide of a metal or metalloid; (MO); a binary oxide; (M1M2O); or a higher order oxide, such as a ternary oxide (M1M2M3O); a sulfide; a nitride; or a halide, such as a chloride or a fluoride.
[0038] By infiltrating the ion conductive matrix with a ceramic material, the ion conductive properties of polymer and dispersed metal salts can be advantageously maintained. By infiltrating the ceramic material into the ion conductive matrix, an interface with a large surface area is formed. Preferably, ceramics can be present in a gap of 10 m of the ion conductive matrix. Providing a mixed layer with a large interfacial area can improve the bonding between the ceramic material and the matrix. Providing a mixed layer with a large interfacial area can improve the ionic conductivity in the layer. For example, ions can preferentially diffuse along the interface between the ceramic domain and the matrix material.
[0039] Providing a ceramic material to the solid electrolyte 10 can improve the contact between the solid electrolyte 10 and other functional layers (e.g., electrode material layers) in the battery stack, for example, by reducing the interface resistance. In addition, the interface ceramic material can also be selected so as to have an enhanced ion injection behavior to / from the electrode; at least better than the intrinsic polymer electrode ion injection characteristics. For example, providing a solid electrolyte 10 at a surface for contacting a negative electrode material (e.g., metallic lithium) with a suitable mixed layer can reduce the interface resistance. Alternatively or in addition, an interface ceramic material can be selected so as to have an enhanced ion injection behavior to / from the electrode. A battery in which the solid electrolyte 10 is provided with a mixed layer at the interface for connection to the negative electrode can have improved performance at low temperatures, for example, during a charging cycle. This improved performance may be the result of reduced contact resistance. In addition, due to the improved uniformity of the electric field at the interface between the negative electrode and the solid electrolyte 10, such a battery can have improved charging characteristics. Providing a mixed layer with small ceramic domains can further improve the effect. Alternatively or in addition, providing a ceramic material to the solid electrolyte 10 can improve the mechanical contact between the interface and the layers in the battery stack, for example, improve adhesion. Improved mechanical contact can mitigate damage to the battery stack, such as damage caused by delamination of functional layers. Alternatively or additionally, providing a ceramic material to the solid electrolyte 10 can improve the mechanical properties of the solid electrolyte. This can improve the handling of the layers of the solid electrolyte 10 and reduce the risk of damage to the solid electrolyte 10, such as due to tearing.
[0040] In some embodiments, both sides of the ion-conducting matrix 10m for connection to the electrode are infiltrated by ceramic materials C1, C2 to form the first and second mixed layers 10h1, 10h2. The second mixed layer may include the same ceramic material as the first mixed layer. Alternatively, the second mixed layer may include a second ceramic material C2. By providing different ceramic materials to the second mixed layer, a solid electrolyte 10 can be formed, wherein the adhesion and electrical properties of the face of the solid electrolyte 10 for connection to the negative electrode and the face of the solid electrolyte 10 for connection to the positive electrode can be independently adjusted. The thickness of the first mixed layer and the second mixed layer can be different and adjusted independently of each other, wherein each layer includes at least 1% of the thickness of the ion-conducting matrix 10m. Optionally, these mixed layers can be both thick or thicker individually, for example 5%, 20%, 50% or more, up to 99%, for example extending all the way to the opposite mixed layer.
[0041] In a specific case, infiltration of the polymer matrix with ceramic materials on the side facing the Li metal improves the cycling stability and can alleviate safety concerns.
[0042] The ceramic material can be a ceramic Li-ion electrolyte, such as LiPO(N), or an oxide, such as TiO2, AlxOy, ZrOx, ZnOy, or a lithium salt. This can improve the cycle stability by improving the mechanical strength of the membrane as well as favorable interface dynamics. As another aspect, a high dielectric ceramic material with a dielectric constant >20 or even >200 can be selected to homogenize Li metal growth by dielectric screening and prevent dendrite growth.
[0043] Furthermore, combining two ceramic materials, such as a high dielectric and a Li-ion electrolyte, in a 2-step process can be used to combine the benefits of both
[0044] The specific implementation plan consists of the following:
[0045] 1. Copper foil substrate coated with Li metal layer with thickness <4 μm (on both sides).
[0046] 2. The polymer membrane infiltrated by the ceramic material at the side facing the Li metal layer is then stacked, for example by but not limited to hot pressing. Additional adhesion / wetting layers (such as gel or plastic electrolytes, or liquid electrolytes or ionic liquids) may be deposited onto the Li metal / membrane before stacking to improve adhesion and interface dynamics.
[0047] In another or other preferred embodiment, the solid electrolyte 10 further has one or more covering layers 10c. These covering layers can be provided to one or more faces for connection to an electrode. The one or more covering layers preferably include ion conductive ceramic materials. For the covering layer provided to the face for connection to the negative electrode, or or in addition, the covering layer may include a ceramic material that forms an ion conductive material by reaction between the ceramic material and the negative electrode material. In some preferred embodiments, the two faces of the solid electrolyte 10 for connection to an electrode are provided with covering layers, wherein the first covering layer and the second covering layer may include the same or different covering materials.
[0048] The ceramic material contained in one or more covering layers may include one or more of the following: ion-conductive ceramic material; and ceramic material, which forms ion-conductive material by reaction between the ceramic material and negative electrode material. The ceramic material contained in one or more mixed layers may also include one or more of the following: ion-conductive ceramic material; and ceramic material, which forms ion-conductive material by reaction between the ceramic material and negative electrode material. Alternatively, the ceramic material contained in one or more mixed layers may also include a material that is not ion-conductive. In this case, the ionic conductivity in the mixed layer can be provided by one or more ion-conductive matrices 10m and the interface between the ceramic and the ion-conductive matrix. Preferably, the covering layer includes a ceramic material that provides a good interface with the corresponding electrode material that can be in contact with it. By providing a suitable covering layer to the solid electrolyte 10, a battery having improved interfacial properties between the solid electrolyte 10 and the positive electrode material and / or between the solid electrolyte 10 and the negative electrode material can be manufactured. The improved interface properties can be classified by improved adhesion, such as adhesion strength and / or reduced contact resistance and / or improved ionic conductivity and / or improved (electro-)chemical stability and / or mitigation of dendrite penetration.
[0049] Therefore, the interfacial stability and ion dynamics on the cathode side of the Li-ion battery can be improved. For example, the polymer membrane may have limited stability to high-voltage (>3.8V) cathode materials. To improve the stability, oxides such as TiO2, AlxOy, ZrOx or ceramic Li-ion electrolytes with high stability to high-voltage materials can be selected as ceramic materials to permeate the side facing the cathode.
[0050] A specific example of this type of heap is:
[0051] 1. A porous cathode layer is deposited on a metal substrate, which includes cathode material (eg NMC, LMNO, LCO), carbon black, and a binder.
[0052] 2. The porous cathode layer can be filled with a cathode electrolyte that has good stability at the cathode interface, such as a liquid electrolyte, an ionic liquid, or a plastic electrolyte.
[0053] 3. A hybrid polymer membrane infiltrated with a ceramic material on the side facing the cathode is stacked to act as a separator between the cathode and anode, for example by hot pressing. The ceramic material improves stability at the contact point with the cathode.
[0054] Preferably, the ceramic material forming the covering layer is selected to form a covering layer having good adhesion (e.g., wettability) to the electrode material. In some embodiments in which the solid electrolyte 10 is used with a lithium metal negative electrode, the solid electrolyte 10 is preferably provided with a covering comprising a lithium-philic material. By providing a solid electrolyte 10 having a lithium-philic covering layer, a lithium battery can be manufactured in which a more uniform lithium electrode can be formed, for example, during the first charging cycle. In an embodiment in which the covering layer is provided to the face of the solid electrolyte 10 for connection to the metal electrode, the covering preferably has a modulus higher than that of the negative metal electrode. For example, for a solid electrolyte for a lithium metal battery, the hardness of the covering layer preferably exceeds 4.9 GPa. By providing a covering layer having a hardness exceeding the hardness of the metal electrode to the solid electrolyte (10), the formation of dendrites can be mitigated.
[0055] In other or further embodiments, an additional ceramic covering is provided on the first covering layer to form a laminated multilayer solid electrolyte 10, such as a solid electrolyte (10) comprising a stack of covering layers, wherein the additional ceramic covering material is ionically conductive or the reaction product of the metal electrode material and the additional ceramic covering material is ionically conductive.
[0056] Figures 2A-2D Schematically shown are cross-sectional views of four embodiments of a solid-state electrolyte 10 incorporating one or more of the above-described features. Figure 2A An exemplary embodiment of a solid-state electrolyte 10 is depicted, wherein two opposing faces of an ion-conducting matrix 10m are provided with mixed layers 10h1 and 10h2 having different thicknesses z1 and z2. Figure 2B An exemplary embodiment of a solid-state electrolyte 10 is depicted, wherein two opposing faces of an ion-conducting matrix 10m are provided with mixed layers, and wherein one of the faces of the solid-state electrolyte 10 is also provided with a ceramic cover layer 10c. Figure 2C An exemplary embodiment of a solid electrolyte 10 is described that includes a capping layer and a mixed layer on a first face of the solid electrolyte 10 and a second capping layer 10c on an opposing face. Figure 2D An exemplary embodiment of a solid electrolyte 10 is depicted, wherein the mixed layer permeates throughout the thickness of the ion-conducting matrix, and wherein the permeated ion-conducting matrix 10m is also provided with first and second covering layers 10c1, 10c2 on opposite sides. It should be understood that the exemplary embodiment described should not be understood as a limiting example. The present invention also relates to a solid electrolyte 10 comprising different or additional combinations of ion-conducting matrix, mixed layer and ceramic covering layer.
[0057] In a preferred embodiment, the ion conductive matrix 10m may be provided with a first ceramic cover at the face for connection with the negative electrode material (anode), and may be impregnated with a second ceramic material at the face for connection with the positive electrode material (cathode). In another or other preferred embodiment, the ion conductive matrix 10m may be provided with a first ceramic cover at the face for connection with the positive electrode material (cathode), and may be impregnated with a second ceramic material at the face for connection with the negative electrode material (anode). In some embodiments, the solid electrolyte 10 includes a cover layer at both faces of the ion conductive matrix 10m for connection with the electrode.
[0058] It should be understood that the same ceramic material can be used to form one or more mixed layers and one or more covering layers. Advantageously, the ceramic material contained in the mixed layer and / or covering layer can be independently selected. By impregnating and covering the solid electrolyte 10 with different ceramic materials, the conductive and interfacial properties of the formed solid electrolyte can be independently optimized. For example, a first ceramic material can be selected to impregnate the ion conductive matrix 10m, and a second ceramic material that may be different can be selected to obtain the best mechanical properties and / or the best contact resistance at the interface with the electrode material.
[0059] In one embodiment, for example, Figure 3A As shown, the present disclosure also relates to a multilayer solid electrolyte 20. The multilayer solid electrolyte can be formed by a stack of two or more solid electrolyte layers 10 according to the present invention. In the exemplary embodiment shown, the multilayer solid electrolyte includes three ion conductive matrices 10m, 11m and 12m, three mixed layers 10h, 11h and 12h, and three covering layers 10c, 11c and 12c. It should be understood that the multilayer solid electrolyte 20 is not limited to the embodiment shown. As described herein, other stacks formed by two or more of any solid electrolyte 10 are also as envisioned.
[0060] It should also be understood that aspects of the present invention also relate to a battery comprising a solid electrolyte 10 according to any one of the preceding claims. Figure 3AAs shown, the battery 102 is formed with a substantially 2D layered structure. An exemplary 2D battery stack is shown in a cross-sectional view and includes a negative electrode layer 2 connected to a current collector 2c; a positive electrode layer 3 connected to a current collector 3c; and a solid electrolyte 10 according to any of the solid electrolytes 10 described herein. Advantageously, the method for manufacturing the solid electrolyte 10 according to the present invention can also be compatible with the method for manufacturing a 3D battery. 3D batteries generally include a structured current collector formed by a base structure, the base structure including an array of conductive elements spaced a certain distance from each other and extending in a direction away from the base. On these elements, other functional layers, such as electrodes and / or electrolytes, are preferably provided in a conformal manner, so that the 3D battery includes a larger interface area between the functional layers and can provide a larger current than the corresponding 2D battery. Therefore, in another or other embodiment, the present disclosure also relates to a battery 103 including a 3D current collector structure, wherein at least one electrode material largely follows the 3D structure. Optionally, more layers in the stack at least partially follow the 3D structure. Figure 3C A cross-sectional view of a 3D battery is depicted, comprising a negative electrode layer 2 connected to a 3D structured current collector 2c; a positive electrode layer 3 connected to a current collector 3c; and a solid electrolyte 10 according to any of the solid electrolytes of the present invention. In some preferred embodiments, the battery comprises: a negative electrode comprising metallic lithium, a metal salt comprising lithium ions. Preferably, in such a battery, the solid electrolyte 10 may have a ceramic coating comprising a lithium-philic material.
[0061] Aspects of the present disclosure also relate to methods for making solid electrolytes. In one embodiment, the manufacturing method includes obtaining an ion-conducting matrix 10m, which includes a polymer P and a metal salt S dispersed in the ion-conducting matrix. Preferably, the ion-conducting matrix 10m can be obtained in the form of a membrane, wherein the membrane can be arranged on a carrier substrate, or alternatively, the ion-conducting matrix can be arranged as a separate membrane. The method for making the disclosed solid electrolyte also includes supplying the ion-conducting matrix 10m to a workbench where the layer is impregnated with a ceramic material. In a preferred embodiment, the impregnation can be performed by chemical vapor infiltration. Chemical vapor infiltration includes exposing the face of the ion-conducting matrix 10m to a gas-phase ceramic precursor material. The gas-phase ceramic precursor material infiltrates into the ion-conducting matrix 10m and reacts with a co-reactant to form a mixed layer. Optionally, the ceramic precursor material infiltrates the ion-conducting matrix 10m over the entire thickness of the matrix to form a mixed layer extending over the entire thickness of the ion-conducting matrix 10m. Suitable ceramic precursor materials typically include metal organic compounds with low vapor pressure. Suitable co-reactants can be selected from water, H2S and oxidizing plasma. The co-reactant may also be provided in the gas phase.
[0062] The ion-conducting matrix 10m may be disposed on a substrate. Alternatively, the solid electrolyte 10 may be manufactured using a separate ion-conducting matrix 10m membrane. Optionally, the method for manufacturing the solid electrolyte 10 may be integrated into a method for manufacturing a battery comprising the solid electrolyte 10 according to any one of the preceding claims. For example, the substrate may include one or more of a current collector and an electrode material (e.g., an intermediate product in a layer-by-layer production process of a layered battery).
[0063] In a preferred embodiment, the infiltration process is carried out using a chemical vapor deposition process (e.g., chemical vapor deposition (CVD), physical vapor deposition (PVD) and atomic layer deposition (ALD) or spatially resolved forms thereof (sALD)) or a gas phase reaction within the matrix. Alternatively or in addition, the infiltration process can be carried out using a wet chemical process. Preferably, the ceramic precursor material and / or co-reactant is added in a time- or space-resolved manner. By providing the ceramic precursor material and / or co-reactant in a time- or space-resolved manner, control over the reaction process, such as the amount of ceramic material formed and the penetration depth, can be obtained. By using the sALD process, the manufacture of the solid electrolyte (10) can be advantageously integrated into a roll-to-roll production process.
[0064] Without wishing to be bound by theory, it is believed that one or more aspects (i-vi) allow the formation of a mixed layer: (i) by exposing a face of the ion-conducting matrix 10m to a ceramic precursor material, such as a vapor phase ceramic precursor material, the precursor material can penetrate into the interior of the matrix, such as penetrating into the matrix; (ii) penetration into the matrix can be facilitated by diffusion of the (vapor phase) precursor material into or along the pores or interstices of the ion-conducting matrix 10m; (iii) within the pores of these interstices, the ceramic precursor material can react with the co-reactant to form the ceramic material; (iv) because the ceramic is formed in the pores or interstices of the matrix, such as between adjacent chains of a polymer contained in the matrix, the ceramic domains formed can be small, such as the ceramic domains formed can have a mesoscopic size, such as a diameter; (v) the co-reactant can also be provided in the vapor phase, in which case it can also penetrate into the ion-conducting matrix 10m; (vi) by providing the ceramic precursor material and the co-reactant in a time- and / or spatially resolved manner, control over the amount and / or penetration depth of the reactant into the ion-conducting matrix 10m can be obtained.
[0065] The amount of the gas phase ceramic precursor material of the impregnated ion conductive matrix 10m and the depth of its impregnation into the matrix can be controlled by one or more of the exposure concentration and / or pressure, exposure temperature, exposure time and the delay time between continuous exposure. For example, increasing the exposure concentration, pressure and / or time can increase the amount of the ceramic formed. Increasing the delay between continuous exposure can increase the time that the precursor material can diffuse downward into the ion conductive matrix 10m before reacting with the co-reactant, thereby increasing the depth of impregnation. The increased exposure temperature increases the diffusion rate and increases the depth of impregnation accordingly. In some preferred embodiments, water is the expected co-reactant. Alternatively or in addition to providing water to the matrix from the gas phase, the ceramic precursor material can use the water reaction that can be dispersed in the whole ion conductive matrix 10m to form a mixed layer. Advantageously, the polymer P contained in the ion conductive matrix 10m is generally a polyether polymer that absorbs water well. The introduced water can be a residue from the formation or deposition process of the ion conductive matrix 10m. Optionally, the amount of water dispersed in the whole matrix can be controlled by applying one or more pressures and temperature gradients. In other words, a suitable amount of water can be provided to the matrix by controlled drying of a wet ion conductive matrix 10m. By providing a suitable water distribution to the ion conductive matrix 10m, the penetration depth of the ceramic precursor material can be controlled. For example, by partially consuming water from the matrix near its surface, the ceramic vapor can diffuse further downward into the body of the matrix before reacting with water, or in other words, increase the thickness of the mixed layer. By increasing the amount of water throughout the matrix, the reactive vapor can react closer to the surface, thereby reducing the penetration depth, or in other words, reducing the thickness of the mixed layer.
[0066] Reference now Figure 2A , it will be understood that the precursor diffused from the bulk facing the ion-conducting matrix 10m forms a mixed interface layer 10h1, 10h2, wherein the density of the infiltrated ceramic material (expressed as the volume concentration of the ceramic per volume unit of the mixed layer) gradually decreases from an initial value outside the solid electrolyte to a lower value toward the ion-conducting matrix 10m. In some embodiments, the volume concentration of the ceramic material at the interface with the ion-conducting matrix may gradually decrease to zero. In other embodiments, such as where the ceramic precursor is provided from both ends, such as Figure 2DAs shown, the volume concentration in the body of the solid electrolyte can be higher, for example, about five percent higher than the volume concentration at the external interface, or for example more than ten percent or even twenty-five percent. In some specific embodiments, for example, where the precursor is continued to be exposed until the ion-conducting matrix is uniformly saturated, the mixed interface layer formed can have a nearly uniform volume concentration of infiltrated ceramic material. The volume concentration of ceramic material at the face of the ion-conducting matrix for connection to the negative electrode or the positive electrode will generally be higher than the volume concentration of ceramic material at the body of the solid electrolyte. In some embodiments, the volume concentration at the face of the ion-conducting matrix for connection to the negative electrode or the positive electrode will be ten percent or more, for example fifteen percent or thirty percent. In some embodiments, for example, where a ceramic covering layer (such as Figure 2D As shown in FIG. 1 , there may be no boundary between the cover layer and the mixed layer, that is, the mixed layer may be understood as gradually continuing into the cover layer. In other words, the volume concentration of the ceramic material at the face of the ion-conducting matrix for connection to the negative electrode or the positive electrode may be almost 100 percent.
[0067] In addition, as the ceramic precursor material reacts to form the ceramic material, they gradually diffuse to a deeper depth through the ion conductive matrix, and the formed ceramic domain can have a shape similar to the diffusion path. For example, in a uniform or dense ion conductive matrix, a diffusion path can exist, for example, in the form of a gap space, such as a void, which can, for example, exist between adjacent polymer chains contained in the medium. Therefore, the formed ceramic material can take an elongated form, which includes at least one dimension on a mesoscopic scale and another dimension along the diffusion path, which is longer than the first dimension, preferably at least 5 times, more preferably, for example, at least 10 times or even 50 times. Since ions may preferentially diffuse along the interface between the ceramic domain and the matrix material, providing an interconnected network of elongated domains or ceramic materials can improve the ionic conductivity in the solid electrolyte. The ceramic domain in the mixed layer preferably has at least one dimension, such as a diameter, whose size is greater than the atomic scale but less than the macroscopic scale. For example, as previously described, the mesoscopic dimension can be 1nm to 5μm, preferably 5nm to 1μm, more preferably 10nm to 500nm. The dimension in the other direction can be as long as the thickness of the hybrid interface layer, for example 10 nm to at most 50 μm, more preferably 50 nm to 20 μm, most preferably 100 nm to 10 μm, for example 250 nm or 1 μm. In addition, in some embodiments, the ceramic domains can form an interconnected network, i.e., a connected ceramic porous network, in which the opposing parts are separated by an ion-conducting matrix (10 m), which is contrary to a uniform or randomly distributed composite of individual particles in the matrix.
[0068] A continuous layer may be understood to include a layer formed from or comprising a continuous matrix that provides a continuous, i.e., uninterrupted path through the layer from one side (e.g., the top side) to the opposite side (e.g., the bottom side). A continuous path, e.g., an ion diffusion path, is preferably not interrupted by an internal interface layer that may exhibit additional diffusion barriers and / or reduced mechanical properties, e.g., due to possible delamination at such an interface. It should be understood that a continuous layer, e.g., an ion-conducting matrix, may be a composite material, such as a blend or copolymer, and / or may be understood to include inclusions, such as infiltrated ceramic domains.
[0069] In another or other preferred embodiment, the method further comprises providing one or more ceramic covering layers. The ceramic material can be formed by a reaction between a suitable ceramic precursor material and a co-reactant. Preferably, the reactant is provided using a chemical vapor deposition process such as CVD, PVD, ALD and sALD. Alternatively or in addition, the reactant can be provided by a wet chemical technique, including but not limited to: spraying, such as spraying of nanoparticles. Advantageously, the same tool can be used, such as using the same process to perform the formation of the mixed layer and the ceramic covering layer. Optionally, different vapor deposition methods can be used to form the covering layer. Optionally, the covering layer can be formed by different ceramic materials. Optionally, an additional covering layer can be provided on the formed covering layer.
[0070] In some preferred embodiments of the method, one or more of ion-conductive mixed layer formation and capping layer formation are also performed on the second side of the ion-conductive substrate 10m.
[0071] In other or other preferred embodiments, the method further includes depositing electrode materials. Advantageously, the method can be integrated into a method for manufacturing a battery. Therefore, after forming the solid electrolyte 10, the method can include depositing a positive electrode material onto the solid electrolyte 10. Alternatively, a negative electrode material can be deposited after forming the solid electrolyte 10.
[0072] The continuous ion-conducting matrix can also be connected to the negative electrode or the positive electrode by melt infusion of a mixed polymer membrane. A single continuous ion-conducting electrolyte matrix is infiltrated with a ceramic material. The surface with the highest volume ceramic content is deposited, for example, on the first electrode, which can be a cathode or an anode, and which has a thickness of, for example, tens of microns up to 200 μm, with a porosity of 20% to 95%. Then, the side of the mixed polymer membrane without or with a lower concentration of ceramic material can be infiltrated into the pores of the first electrode using a melt infiltration process. By increasing the temperature to near or slightly above the melting temperature of the conductive matrix and applying pressure at the same time, the side facing the first electrode melts and can penetrate into the pores of the first electrode matrix, while the side with more infiltrated ceramic material facing away from the first electrode has a higher T 熔化 and remain in a solid / glassy / rubbery state.
[0073] The penetration depth of the ceramic electrolyte may typically be 5 μm or 10 μm or 20 μm.The second electrode may be placed directly on top or an additional electrolyte layer (solid, liquid electrolyte with or without separator) may be used on the second electrode side.
[0074] In this embodiment, there may be more than one ceramic material on one side or on both sides, with the main difference between the two sides being the average volume concentration of the ceramic, which is lower on one side of the porous electrode, resulting in infiltration of that portion into the porous electrode.
[0075] Such a process can be repeated to obtain alternating (cathode-anode-cathode) patterned electrodes, which together with the filled single continuous conductive matrix form a 3D battery stack. The electrodes can be porous or non-porous, in the latter case, for example, fully dense electrodes. In addition to the functions described above (conductivity and stability improvement), ceramic materials such as AlxOy, ZrOx infiltrated on the top side can protect the 3D battery stack from degradation when in contact with rich O, N, H2O environments.
[0076] The porous electrode can be filled with a single continuous ion conducting matrix which can extend for example 1 um, 5 um, 10 um, 20 um and 40 um on top of the cathode material. The membrane is then exposed to a vapor deposition process to produce an infiltrated ceramic material on the top side. The ceramic material can be a solid electrolyte such as LIPON, LAGP or an oxide such as AlxOy, TiOx, ZnOx, ZrOx, Li salts, or a combination thereof.
Claims
1. A solid electrolyte (10) for providing an ionically conductive connection between a negative electrode and a positive electrode in a battery, the solid electrolyte (10) comprising: - a continuous ion-conducting matrix (10m) comprising a polymer (P), - a metal salt (S) dispersed in said ion-conducting matrix (10m), and - a first ceramic material (C1), At least one side of the ion conductive matrix (10m) for connection to the negative electrode or the positive electrode is infiltrated by the first ceramic material (C1) to form a first mixed interface layer (10h1) with improved ion conductivity between at least one of the negative electrode and the positive electrode in the battery and the ion conductive matrix (10m), wherein the volume concentration of the first ceramic material (C1) per volume unit of the first mixed interface layer (10h1) gradually decreases from an initial value at the outside of the solid electrolyte (10) to a lower value toward the ion conductive matrix (10m).
2. The solid electrolyte (10) according to claim 1, wherein both sides of the ion-conducting matrix (10m) for connection to the electrode are infiltrated by ceramic materials (C1, C2) to form a first mixed interface layer (10h1) and a second mixed interface layer (10h2), wherein the second mixed interface layer (10h2) comprises a second ceramic material (C2), or comprises the same ceramic material as the first mixed interface layer (10h1).
3. The solid electrolyte (10) according to claim 1 or 2, wherein one or more faces of the ion-conducting matrix (10m) for connection to the electrode are provided with a first covering layer (10c), wherein the first covering layer (10c) comprises one or more of the following: - ion-conducting ceramic materials, and - A ceramic material that reacts with the negative electrode material to form an ionically conductive material.
4. The solid electrolyte (10) according to claim 3, wherein: The ion conductive substrate (10m) is provided with the first covering layer (10c1) at the surface for connection with the negative electrode material, and is impregnated with the second ceramic material at the surface for connection with the positive electrode material.
5. The solid electrolyte (10) according to claim 3, wherein the ion conductive matrix (10m) is provided with the first covering layer (10c1) at the surface for connection with the positive electrode material, and is impregnated with a second ceramic material at the surface for connection with the negative electrode material.
6. The solid electrolyte (10) according to claim 3, wherein: Both sides of the ion-conducting substrate (10m) for connection to the electrodes are provided with covering layers (10c1, 10c2).
7. A multilayer solid-state electrolyte formed by a stack of solid-state electrolyte layers (10) according to any one of the preceding claims.
8. A battery (100) comprising a solid electrolyte (10) according to any one of the preceding claims, the solid electrolyte (10) being arranged between a positive electrode (3) and a negative electrode (2).
9. The battery of claim 8, wherein the negative electrode comprises lithium, the metal salt comprises lithium ions, and wherein the ceramic coating facing the negative electrode comprises a lithiophilic material.
10. A method for producing a solid-state electrolyte (10) according to any one of the preceding claims, the method comprising: - providing an ion-conducting matrix (10m) comprising a polymer (P) and a dispersed metal salt (S); - supplying the ion-conducting matrix (10m) to a station for impregnating the layer with ceramic material; as well as - exposing the first side of the ion-conducting matrix (10m) to a vapor-phase ceramic precursor material using a chemical vapor impregnation method, wherein the vapor phase ceramic precursor material infiltrates into the ion conductive matrix (10m) and reacts with a co-reactant to form a mixed interface layer, the mixed interface layer being suitable for forming an interface layer having improved ion conductivity between at least one of a negative electrode and a positive electrode in a battery and the ion conductive matrix included in the battery, The co-reactant is one or more of the group consisting of water, hydrogen sulfide and oxidizing plasma.
11. The method of claim 10, wherein the chemical vapor impregnation method is selected from one or more of chemical vapor deposition (CVD), atomic layer deposition (ALD) and spatially resolved ALD (sALD), wherein the impregnation depth of the vapor phase ceramic precursor material is controlled by one or more of exposure concentration and / or pressure, exposure temperature, exposure time and delay time between consecutive exposures.
12. The method of claim 11, wherein the chemical vapor immersion method is sALD.
13. The method according to claim 10 or 11, wherein the method further comprises providing a ceramic covering layer on one or more faces of the ion-conducting matrix (10m) for connection to the electrode.
14. The method according to claim 10 or 11, wherein the method further comprises providing a ceramic covering layer on one or more faces of the ion conductive substrate (10m) for connection to the electrode, wherein one or more of the mixed interface layer forming step and the covering layer forming step are also performed on a second face of the ion conductive substrate (10m).
15. The method of claim 10 or 11, wherein the method further comprises depositing a positive electrode material and a negative electrode material.
16. The method according to claim 10 or 11, wherein the mixed interface layer forming step is also performed on the second side of the ion conductive matrix (10m).
Citation Information
Patent Citations
Composite solid electrolyte, and preparation method and applications thereof
CN108598560A
Composite electrolyte for secondary battery, having multi-layer structure
CN108886164A
Composite polymer electrolyte for lithium secondary battery containing single ion conductor and method of manufacturing it
CN1610170A
Lithium ion conducting inorganic filler-containing composite polymer electrolyte for lithium secondary battery and method for manufacturing the same
EP1598896A1
High-performance ceramic-polymer separators for lithium batteries
US20180026302A1